Ruptured hydatid cyst presenting as recurrent pneumothorax with co-existing pulmonary tuberculosis and uniportal thoracoscopic management: first Indian report - Klein, Dantis; G. Ranganath, Thippanahalli (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2021)
Hydatid cyst is a common dsease in developing countries caused by Echinococcus granulosus, affecting mainly the liver and lungs with a prevalence rate of 5–10% in endemic parts of Asia [1]. According to the global tuberculosis report 2020, tuberculosis is one of the top ten causes of death worldwide, accounting for 10 million cases, with India bearing a 26% global burden [2]. Ruptured hydatid cyst is a diagnostic challenge, radiologically presenting as a recurrent pneumothorax with an incidence rate of 2.4–6.2%, while co-existing pulmonary tuberculosis (PTB) with ruptured hydatid cyst and a recurrent pneumothorax has been rarely reported in the literature [3]. With no reports to date, we hereby report a tri-combination of ruptured hydatid cyst presenting as a recurrent pneumothorax with co-existing pulmonary tuberculosis and uniportal thoracoscopic management.